Evidence-based crisis standards of care for out-of-hospital cardiac arrests in a pandemic. (November 2020) - Natalzia, Peter; Murk, William; Thompson, Jeffrey J.; Dorsett, Maia; Cushman, Jeremy T.; Reed, Philip; Clemency, Brian M.; ,
Abstract: Background & purpose: Pandemics such as COVID-19 can lead to severe shortages in healthcare resources, requiring the development of evidence-based Crisis Standard of Care (CSC) protocols. A protocol that limits the resuscitation of out-of-hospital cardiac arrests (OHCA) to events that are more likely to result in a positive outcome can lower hospital burdens and reduce emergency medical services resources and infection risk, although it would come at the cost of lives lost that could otherwise be saved. Our primary objective was to evaluate candidate OHCA CSC protocols involving known predictors of survival and identify the protocol that results in the smallest resource burden, as measured by the number of hospitalizations required per favorable OHCA outcome achieved. Our secondary objective was to describe the effects of the CSC protocols in terms of health outcomes and other measures of resource burden. Methods: We conducted a retrospective cohort study of adult patients in the Cardiac Arrest Registry to Enhance Survival (CARES) database. Non-traumatic OHCA events from 2018 were included (n = 79, 533). Candidate CSC protocols involving combinations of known predictors of good survival for OHCA were applied to the existing dataset to measure the resulting numbers of resuscitation attempts, transportations to hospital, hospital admissions, and favorable neurological outcomes. These outcomes were also assessed under Standard Care, defined as no CSC protocol applied to the data. Results: The CSC protocol with the smallest number of hospitalizations per survivor with a favorable neurological outcome was that an OHCA resuscitation should only be attempted if the arrest was witnessed by emergency medical services or the first monitored rhythm was shockable (number of hospitalizations: 2.26 [95% CI: 2.21–2.31] vs. 3.46 [95% CI: 3.39–3.53] under Standard Care). This rule resulted in significant reductions in resource utilization (46.1% of hospitalizations and 29.2% of resuscitation attempts compared to Standard Care) while still preserving 70.5% of the favorable neurological outcomes under Standard Care. For every favorable neurological outcome lost under this CSC protocol, 6.3 hospital beds were made free that could be used to treat other patients. Conclusion: In a pandemic scenario, pre-hospital CSC protocols that might not otherwise be considered have the potential to greatly improve overall survival, and this study provides an evidence-based approach towards selecting such a protocol. As this study was performed using data generated before the COVID-19 pandemic, future studies incorporating pandemic-era data will further help develop evidence-based CSC protocols.